2020
DOI: 10.1002/ajb2.1508
|View full text |Cite
|
Sign up to set email alerts
|

Endopolyploidy is associated with leaf functional traits and climate variation in Arabidopsis thaliana

Abstract: PremiseEndopolyploidy is widespread throughout the tree of life and is especially prevalent in herbaceous angiosperms. Its prevalence in this clade suggests that endopolyploidy may be adaptive, but its functional roles are poorly understood. To address this gap in knowledge, we explored whether endopolyploidy was associated with climatic factors and correlated with phenotypic traits related to growth.MethodsWe sampled stem and leaf endopolyploidy in 56 geographically separated accessions of Arabidopsis thalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Contrary to our expectation, our study indeed revealed differences in endoreduplication between our pairs of foothill vs. alpine ecotypes, but the effect was not consistent across all pairs and exhibited rather regional‐ and treatment‐specific patterns. Our results are in line with other studies of A. thaliana where no clear association was found between endoreduplication and major environmental clines such as latitude (Gegas et al, 2014; Pacey et al, 2020a) and point to population‐specific patterns. Hence, despite an effect of single environmental factors on endoreduplication (i.e., UV‐B radiation), constitutive differences driven by environmental clines were generally weak, and the regional‐ or population‐specific patterns observed may also reflect a contribution of the local environment (and may involve different sets of genes) and/or of the lineage‐specific genetic background.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Contrary to our expectation, our study indeed revealed differences in endoreduplication between our pairs of foothill vs. alpine ecotypes, but the effect was not consistent across all pairs and exhibited rather regional‐ and treatment‐specific patterns. Our results are in line with other studies of A. thaliana where no clear association was found between endoreduplication and major environmental clines such as latitude (Gegas et al, 2014; Pacey et al, 2020a) and point to population‐specific patterns. Hence, despite an effect of single environmental factors on endoreduplication (i.e., UV‐B radiation), constitutive differences driven by environmental clines were generally weak, and the regional‐ or population‐specific patterns observed may also reflect a contribution of the local environment (and may involve different sets of genes) and/or of the lineage‐specific genetic background.…”
Section: Discussionsupporting
confidence: 93%
“…Our analyses thus informed on the endoreduplication level at a specific time of the elongation phase of the leaf of young A. arenosa plant. Because endoreduplication is correlated with the size of the leaf at the time of sampling (Pacey et al, 2020a), prior to analysis, we approximated the area of the selected leaf by multiplying leaf length by leaf width. Plants were processed generally following the same procedure as described by Kolář et al (2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, development of vegetative tissues often involves rounds of DNA replications without cell division, resulting in large increases in nuclear ploidy (known as endoreduplication or endopolyploidy). Therefore, even more so than other eukaryotic lineages, plants may have evolved regulatory responses that coordinate mitochondrial and plastid function with changes in nuclear ploidy and cell size (Kawade et al, 2013;Pacey et al, 2020;He et al, 2021).…”
Section: Why Don't Plant Polyploids Exhibit More Genome-wide Signatur...mentioning
confidence: 99%